2014
DOI: 10.1158/1538-7445.am2014-1321
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 1321: Identification of markers of sensitivity and resistance to palbociclib (PD0332991) in melanoma

Abstract: Background: Melanoma, a malignancy originating in pigment-producing melanocytes, is generally resistant to conventional treatments such as radiotherapy or chemotherapy. Molecular targeted therapeutics against BRAF and MEK have shown marked efficacy for patients with metastatic melanoma. However these targeted therapies have a limited duration of response. Palbociclib is a highly selective inhibitor of cyclin dependent kinases 4 and 6 (CDK4/6) that has been shown to inhibit growth of malignant cell lines in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In vitro studies have suggested Rb, cyclin D1, E2F transcription factor 1 and members of the inhibitors of CDK4 family (p16, p15) as potential biomarkers to identify response to palbociclib [12,17,21], and the genomic and expression markers of activation of the hedgehog/smoothened pathway as strong predictors of resistance to palbociclib [22].…”
Section: Scientific Summary 21 Pharmacodynamicsmentioning
confidence: 99%
“…In vitro studies have suggested Rb, cyclin D1, E2F transcription factor 1 and members of the inhibitors of CDK4 family (p16, p15) as potential biomarkers to identify response to palbociclib [12,17,21], and the genomic and expression markers of activation of the hedgehog/smoothened pathway as strong predictors of resistance to palbociclib [22].…”
Section: Scientific Summary 21 Pharmacodynamicsmentioning
confidence: 99%